APPLICATION OF K-MEANS CLUSTERING ALGORITHM TO ANALYZE INSURANCE COMPANY BUSINESS (CASE STUDY: PT. JASINDO INSURANCE) - Elni Arbaeti, Endang; Hara Pardede, Akim Manaor; Nur Kadim, Lina Arliana (Yayasan Bina Internusa Mabarindo, 2023)
Asuransi Jasindo is an insurance company that accepts insurance coverage, both directly and indirectly, with the ownership of 1 series A dwiwarna share owned by the Republic of Indonesia and 424,999 Series B shares owned by PT Bahana Pembinaan Usaha Indonesia (Persero). PT Asuransi Jasa Indonesia or known as Asuransi Jasindo, has a qualified, long and mature experience in the field of general insurance even since the colonial era. This experience provides its own pioneering value for the existence and growth of Asuransi Jasindo's performance to date, so that it has succeeded in gaining public trust both at home and abroad. PT Asuransi Jasa Indonesia has several products and options in choosing which insurance is needed by customers, both agriculture, health, education and many more. Due to the large amount of insurance data, it is difficult for companies to process existing data and information. Therefore the author wants to create an application that can help companies process and classify existing insurance user data to produce information that can make it easier for insurers to provide better service to meet insurance user satisfaction using the K-Means Algorithm method. Of the 1089 data analyzed, the results that were most widely used were insurance data with ages 26-35 years, located in the Medan city sub-district with the type of insurance used, namely Jasindo Micro insurance.